Ternary precursor with high specific surface area and low sodium-sulfur content as well as preparation method and application of ternary precursor

The preparation of high-specific sodium-sulfur ternary precursors with low-specific sodium-sulfur precursors was solved through a two-step co-precipitation reaction process, which solved the problems of uneven particle size distribution and poor batch stability in the prior art, and achieved more stable battery performance.

CN119637960AActive Publication Date: 2025-03-18MCC RAMU NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411700167.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-18
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

In the production of high-specific low-voltage sodium-sulfur ternary precursors, the particle size distribution and poor batch stability are caused by poor cycle life and stability of the battery.

Method used

Using a two-step co-precipitation reaction process, firstly, crystal nuclei with a particle size of 1.0 μm to 1.6 μm was prepared in the first reactor, and then in the second reactor, co-precipitation reaction was performed under an inert atmosphere, and then under an oxidation atmosphere, to obtain a high-specific low sodium-sulfur ternary precursor with D50 of 3.8 μm to 4.2 μm.

Benefits of technology

Through this process, the particle size distribution of the ternary precursor is significantly reduced, the control stability of the growth process and the consistency of product batches are improved, and process indicators such as tap density, specific surface area and particle size distribution are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637960A_ABST
    Figure CN119637960A_ABST
Patent Text Reader

Abstract

The invention discloses a high-specific-surface-area low-sodium-sulfur ternary precursor as well as a preparation method and application thereof. The preparation method comprises the following steps: adding a nickel-cobalt-manganese salt solution, a precipitant and a complexing agent into a first reaction kettle, and carrying out a co-precipitation reaction in an inert atmosphere to obtain a crystal nucleus with the particle size D50 of 1.0-1.6 [mu] m; and adding the crystal nucleus, a nickel-cobalt-manganese salt solution, a precipitator and a complexing agent into a second reaction kettle, carrying out a coprecipitation reaction in an inert atmosphere, then carrying out a coprecipitation reaction in an oxidizing atmosphere, and stopping the reaction when the product granularity D50 is 3.8-4.2 microns to obtain the high-specific-surface-area low-sodium-sulfur ternary precursor. The ternary precursor prepared by the method is narrow in particle size distribution and good in sphericity, primary particles are flaky and grow in the radial direction, secondary particles are porous, the product batch stability is high, and production operation is convenient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a high specific surface area, low sodium and sulfur ternary precursor, and a preparation method and application thereof. Background Art

[0002] As a key component of lithium-ion batteries, lithium-ion battery cathode materials have a decisive influence on the electrochemical performance of batteries. In recent years, layered Ni-Co-Mn ternary composite materials have been widely used in the field of electric vehicles due to their high specific capacity, low cost, and long cycle life. As the raw material for the preparation of ternary cathode materials, ternary precursors largely determine the performance of ternary cathode materials. At present, the mainstream method for industrial production of ternary precursors is co-precipitation. The particle size, tap density, specific surface area, morphology, etc. of ternary precursors play a decisive role in the performance of ternary cathode materials. High specific surface area, low sodium sulfur ternary precursors can provide more active sites with a high specific surface area. When the nickel content is relatively high, higher capacity can be obtained. At the same time, high specific surface area, low sodium sulfur can also increase the ion transfer rate and electron transfer rate of the material, thereby improving the cycle life and stability of the battery.

[0003] At present, the production of high specific surface area, low sodium-sulfur ternary precursors is mostly low-alkalinity continuous process or pure discontinuous oxidation process. The continuous method has low alkalinity and poor complexation effect, which makes it more difficult to control the product particle size, with a wide particle size distribution, poor batch stability, uneven growth direction and size of primary particles, and irregular secondary particle morphology. The amount of nuclei discharged in the early stage of the pure discontinuous method cannot be accurately controlled, resulting in irregular growth time: if the growth rate is too fast, the product particle size distribution is wide, the sphericity is poor, the twin ball phenomenon is obvious, and the primary particles grow disorderly; if the growth rate is too slow, the primary particles are too thick, the particle gap is too small, the product tap density is too large, and the specific surface area is too small, resulting in obvious ball breakage during the sintering process, affecting the battery capacity and cycle performance. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.

[0005] To this end, the first aspect of the present invention provides a method for preparing a high specific surface area low sodium sulfur ternary precursor, wherein a nickel cobalt manganese salt solution, a precipitant and a complexing agent are added to a first reaction kettle, and a coprecipitation reaction is carried out under an inert atmosphere to obtain a crystal nucleus with a particle size D50 of 1.0 μm to 1.6 μm;

[0006] The crystal nuclei, nickel-cobalt-manganese salt solution, precipitant and complexing agent are added to a second reaction kettle, and a coprecipitation reaction is first carried out under an inert atmosphere and then under an oxidizing atmosphere. The reaction is stopped when the product particle size D50 is 3.8 μm to 4.2 μm to obtain the high specific surface area low sodium sulfur ternary precursor.

[0007] Furthermore, the coprecipitation reaction in the first reactor comprises:

[0008] The inlet flow rate of nickel-cobalt-manganese salt solution is 4L / h~6L / h, and the inlet concentration is 1.8mol / L~2.4mol / L;

[0009] The reaction temperature is 60°C to 70°C, the pH value is 11.6 to 11.8, and the homogenization speed is 700rpm to 800rpm.

[0010] Further, the coprecipitation reaction is first carried out under an inert atmosphere, comprising:

[0011] The initial crystal nucleus content of the reaction is 120g / L to 130g / L;

[0012] The inlet flow rate of nickel-cobalt-manganese salt solution is 2L / h~4L / h, and the inlet concentration is 1.8mol / L~2.4mol / L;

[0013] The reaction temperature is 60°C to 70°C, the reaction time is 4h to 5h, the pH value is 11.1 to 11.5, and the homogenization speed is 600rpm to 700rpm.

[0014] Further, the coprecipitation reaction is carried out under an oxidizing atmosphere, comprising:

[0015] Increase the flow rate of nickel-cobalt-manganese salt solution by 0.5L / h to 1L / h every 4 to 12 hours;

[0016] Reduce the homogenization speed by 2rpm to 10rpm every 4 to 12 hours;

[0017] Lower the reaction pH by 0.02 to 0.04 every 4 to 12 hours;

[0018] Initial air flow rate is 1m 3 / h~3m 3 / h, when the particle size D50 of the product is 2.8μm~3.2μm, increase the air flow rate by 0.4m 3 / h~0.6m 3 / h.

[0019] Furthermore, the precipitant is a sodium hydroxide solution, and the inlet concentration is 6 mol / L to 12 mol / L;

[0020] The complexing agent ammonia solution has an inlet concentration of 4 mol / L to 10 mol / L;

[0021] Controlling the ammonia concentration in the first reaction kettle to be 1 g / L to 5 g / L;

[0022] The ammonia concentration in the second reaction kettle is controlled to be 1 g / L to 5 g / L.

[0023] Furthermore, in the nickel-cobalt-manganese salt solution, the molar ratio of nickel, cobalt and manganese is X:Y:Z, satisfying X+Y+Z=1, and 0.6≤X<1, 0<Y<0.4 and 0<Z<0.4.

[0024] Furthermore, the high specific surface area low sodium sulfur ternary precursor has a specific surface area of ​​18±2m 2 / g, tap density is 1.70±0.2g / cm 3 , particle size distribution diameter is 0.75±0.1, sodium content is <70ppm, sulfur content is <800ppm, and D50 is 4±0.2μm.

[0025] The second aspect of the present invention provides a high specific surface area, low sodium and sulfur ternary precursor, which is obtained by the above-mentioned preparation method of the high specific surface area, low sodium and sulfur ternary precursor.

[0026] According to a third aspect of the present invention, a positive electrode material is provided. The positive electrode material is prepared by mixing the above-mentioned high specific surface area, low sodium and sulfur ternary precursor with a lithium source.

[0027] A fourth aspect of the present invention provides a lithium-ion battery, wherein the positive electrode material of the lithium-ion battery is prepared by mixing the above-mentioned high specific surface area, low sodium and sulfur ternary precursor with a lithium source.

[0028] Beneficial effects:

[0029] The method for preparing a high specific surface area low sodium sulfur ternary precursor provided by the present invention is to prepare a crystal nucleus with a particle size D50 of 1.0 μm to 1.6 μm by a first reactor, and then add the crystal nucleus to a second reactor, first coprecipitate under an inert atmosphere, and then coprecipitate under an oxidizing atmosphere to obtain a ternary precursor with a D50 of 3.8 μm to 4.2 μm. Compared with the prior art, it has at least the following beneficial effects: reducing the particle size distribution of the ternary precursor, improving the control stability of the growth process and the consistency of product batches, the primary particles grow in an orderly manner and are in the form of thin sheets, the secondary particles are porous, the sphericity is good and the number of twin balls is small, thereby improving the process indicators such as tap density, specific surface area, and particle size distribution, and obtaining a high specific surface area low sodium sulfur ternary precursor. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is an SEM image of the high specific surface area, low sodium-sulfur ternary precursor prepared in Example 1 of the present application.

[0031] Figure 2 This is an SEM image of the high specific surface area, low sodium-sulfur ternary precursor prepared in Example 2 of the present application.

[0032] Figure 3This is an SEM image of the high specific surface area, low sodium-sulfur ternary precursor prepared in Example 3 of the present application. DETAILED DESCRIPTION

[0033] In order to better understand the above technical solution, the technical solution of the present application is described in detail below through specific embodiments.

[0034] In a first aspect of an embodiment of the present invention, a method for preparing a high specific surface area low sodium sulfur ternary precursor is provided, wherein a nickel cobalt manganese salt solution, a precipitant and a complexing agent are added to a first reaction kettle, and a coprecipitation reaction is carried out under an inert atmosphere to obtain a crystal nucleus with a particle size D50 of 1.0 μm to 1.6 μm;

[0035] The crystal nuclei, nickel-cobalt-manganese salt solution, precipitant and complexing agent are added to a second reaction kettle, and a coprecipitation reaction is first carried out under an inert atmosphere and then under an oxidizing atmosphere. The reaction is stopped when the product particle size D50 is 3.8 μm to 4.2 μm to obtain the high specific surface area low sodium sulfur ternary precursor.

[0036] The preparation method of the high specific surface area low sodium sulfur ternary precursor provided by the embodiment of the present invention adopts a quantitative nucleation and quantitative oxygen production process, and the production process is mainly divided into two steps: the first step is to prepare a crystal nucleus with a small number of twin balls, a narrow particle size distribution, and a large specific surface area. The production process is a one-stage continuous method. After the base liquid is prepared, the feeding is started, and the feeding is stopped after the particle size index D50 is stable by adjusting the process parameters, and the prepared crystal nucleus is retained for standby; the second step is to prepare a crystal nucleus with good sphericity, a narrower particle size distribution, orderly primary particle growth direction, and large gaps between particles. The production process of the ternary precursor is a pure discontinuous method. Another synthesis kettle is selected to prepare the base liquid, and the crystal nucleus is poured into the synthesis kettle for intermittent concentration reaction. Oxygen is introduced after a period of reaction, and the process parameters are adjusted to change the growth mode and thickness of the primary particles, so that the growth direction of the primary particles is orderly and thin, and the secondary particles are porous. The number of twin balls is small, the sphericity is good, and the consistency is high. When D50 is 3.8μm~4.2μm, the reaction is stopped, and the product is aged, washed, and dried to obtain a high specific surface area and low sodium sulfur precursor.

[0037] The method for preparing a high specific surface area, low sodium and sulfur ternary precursor provided by an embodiment of the present invention reduces the particle size distribution of the ternary precursor compared to the prior art, improves the growth process control stability and product batch consistency, the primary particles grow in an orderly manner and are in the form of thin sheets, the secondary particles are porous, have good sphericity and a small number of twin balls, thereby improving process indicators such as tap density, specific surface area, and particle size distribution, and obtaining a high specific surface area, low sodium and sulfur ternary precursor.

[0038] In some embodiments, the coprecipitation reaction in the first reactor includes: the inlet flow rate of the nickel cobalt manganese salt solution is 4L / h~6L / h, the inlet concentration is 1.8mol / L~2.4mol / L; the reaction temperature is 60℃~70℃, the pH value is 11.6~11.8, and the homogenization speed is 700rpm~800rpm.

[0039] Specifically, before the reaction, according to NiSO4, CoSO 4、 A nickel-cobalt mixed salt solution with a mixed concentration of 1.8 mol / L to 2.4 mol / L is prepared in a ratio of X:Y:Z to MnSO4, wherein X+Y+Z=1, 0.6≤X<1, 0<Y<0.4, 0<Z<0.4, 6 mol / L to 12 mol / L NaOH solution is used as a precipitant and 4 mol / L to 10 mol / L ammonia solution is used as a complexing agent. By controlling the ammonia concentration in the first reaction kettle to be 1 g / L to 5 g / L, the inlet flow rate of the nickel-cobalt-manganese salt solution to be 4 L / h to 6 L / h, the coprecipitation reaction temperature to be 60°C to 70°C, the pH value to be 11.6 to 11.8, and the homogenization speed to be 700 rpm to 800 rpm, crystal nuclei with good sphericity, a small number of twin balls, a solid content of 120 g / L to 130 g / L, and a uniform particle size distribution of D50 of 1.0 μm to 1.6 μm are obtained.

[0040] In some embodiments, the coprecipitation reaction in the second reactor: First, the coprecipitation reaction is carried out under an inert atmosphere, specifically: the initial crystal nucleus content of the reaction is 120g / L~130g / L; the inlet flow rate of the nickel cobalt manganese salt solution is 2L / h~4L / h, and the inlet concentration is 1.8mol / L~2.4mol / L; the reaction temperature is 60℃~70℃, the reaction time is 4h~5h, the pH value is 11.1~11.5, and the homogenization speed is 600rpm~700rpm. Then, the coprecipitation reaction is carried out under an oxidizing atmosphere, specifically: the flow rate of the nickel cobalt manganese salt solution is increased by 0.5L / h~1L / h every 4~12h; the homogenization speed is decreased by 2rpm~10rpm every 4~12h; the reaction pH value is decreased by 0.02~0.04 every 4~12h; the initial air flow rate is 1m 3 / h~3m 3 / h, when the particle size D50 of the product is 2.8μm~3.2μm, increase the air flow rate by 0.4m 3 / h~0.6m 3 / h.

[0041] Specifically, before the reaction, according to NiSO4, CoSO 4、A mixed nickel-cobalt salt solution with a concentration of 1.8 mol / L to 2.4 mol / L is prepared with a ratio of X:Y:Z, wherein X+Y+Z=1, 0.6≤X<1, 0<Y<0.4, 0<Z<0.4, a 6 mol / L to 12 mol / L NaOH solution is used as a precipitant and a 4 mol / L to 10 mol / L ammonia solution is used as a complexing agent, and the ammonia concentration in the second reactor is controlled to be 1 g / L to 5 g / L. First, a coprecipitation reaction is carried out under an inert atmosphere: the inlet flow rate of the nickel-cobalt-manganese salt solution is 2 L / h to 4 L / h, the reaction temperature is 60°C to 70°C, the reaction time is 4h to 5h, the pH value is 11.1 to 11.5, and the homogenization speed is 600 rpm to 700 rpm. Then, the coprecipitation reaction was carried out in an oxidizing atmosphere: the flow rate of the nickel-cobalt-manganese salt solution was increased by 0.5L / h to 1L / h every 4 to 12 hours; the homogenization speed was decreased by 2rpm to 10rpm every 4 to 12 hours; the reaction pH value was decreased by 0.02 to 0.04 every 4 to 12 hours; the initial air flow rate was 1m 3 / h~3m 3 / h, when the particle size D50 of the product is 2.8μm~3.2μm, increase the air flow rate by 0.4m 3 / h~0.6m 3 / h, and stop the reaction when the product particle size D50 reaches 3.8μm~4.2μm, to obtain a high-specific surface area, low-sodium-sulfur ternary precursor with large primary particle gap, high single-pot output and long-speed uniformity.

[0042] In summary, the growth rate of the particles can be controlled by reasonably controlling the ammonia concentration and pH value, reducing the inclusion of sodium and sulfur impurities into the particles during the reaction process, and improving the particle size and thickness and controlling the specific surface area of ​​the particles by controlling and adjusting the coprecipitation reaction parameters under an oxidizing atmosphere. The high specific surface and low sodium and sulfur ternary precursor with a specific surface area of ​​18±2m 2 / g, tap density is 1.70±0.2g / cm 3 , particle size distribution diameter is 0.75±0.1, sodium content is <70ppm, sulfur content is <800ppm, and D50 is 4±0.2μm.

[0043] According to a second aspect of an embodiment of the present invention, a high specific surface area, low sodium and sulfur ternary precursor is provided, which is obtained by using the above-mentioned preparation method of the high specific surface area, low sodium and sulfur ternary precursor.

[0044] According to a third aspect of an embodiment of the present invention, a positive electrode material is provided. The positive electrode material is prepared by mixing the above-mentioned high specific surface area, low sodium and sulfur ternary precursor with a lithium source.

[0045] According to a fourth aspect of the embodiments of the present invention, a lithium-ion battery is provided, wherein the positive electrode material of the lithium-ion battery is prepared by mixing the above-mentioned high specific surface area, low sodium and sulfur ternary precursor with a lithium source.

[0046] Example 1

[0047] A method for preparing a high specific surface area and low sodium sulfur ternary precursor, comprising:

[0048] A 2.1 mol / L nickel-cobalt mixed salt solution was prepared according to the molar ratio of NiSO4, CoSO4, and MnSO4 of 60:10:30, and a 10 mol / L NaOH solution was used as a precipitant and an 8 mol / L ammonia solution was used as a complexing agent. The first reactor and the second reactor were respectively filled with water to the sampling port, and then stirred and the jacket water of the reactor was heated to 65°C. Ammonia solution was injected into the first reactor and the second reactor to prepare the bottom liquid before grooving, and the ammonia concentration in the first reactor and the second reactor was controlled at 4 g / L.

[0049] Coprecipitation reaction in the first reactor: nitrogen flow rate 1.5m 3 / h to ensure that the synthesis reactor is in a nitrogen atmosphere, adjust the homogenization speed to 800rpm, and at the same time start the nickel-cobalt-manganese salt solution pump, the sodium hydroxide solution pump, and the ammonia solution pump for coprecipitation reaction, control the salt liquid inflow to 5L / h, and after the liquid is inflow, stably control the temperature to 65°C, the ammonia concentration to 4g / L, the pH value to 11.7, and stably control the particle size D50 to 1.2μm-1.4μm, the solid content to 120g / L-130g / L, and the sample obtained at this time is a primary particle with moderate thickness and a large flake shape, and a secondary particle with more porous nuclei;

[0050] Coprecipitation reaction in the second reactor: The material of the first reactor was pumped into the second reactor with a calculated pumping amount of 15L. The stirring speed was adjusted to 600rpm. Then, the nickel-cobalt-manganese salt solution pump, the sodium hydroxide solution pump, and the ammonia solution pump were simultaneously used for coprecipitation reaction. The salt inlet was controlled to be 3L / h. After the inlet, the temperature was stabilized at 65°C, the ammonia concentration was 4g / L, the initial pH value was 11.3, and the nitrogen flow rate was 1.5m 3 / h, after 4 hours of reaction, the nitrogen was replaced by air at a flow rate of 2.5m 3 / h, every 4 hours, increase the salt flow rate by 0.6L / h, reduce the stirring speed by 6rpm, and reduce the reaction pH value by 0.04. When the particle size grows to 3μm, adjust the air flow rate to 3m 3 / h, and stop the reaction when the particle size grows to 4μm. The output product is subjected to aging, clear liquid discharge, alkali washing, water washing and drying to obtain a high specific surface area and low sodium sulfur ternary precursor.

[0051] like Figure 1 As shown, the ternary precursor particles prepared in Example 1 have good sphericity, uniform primary particle growth, and moderate porosity.

[0052] The physical properties of the ternary precursor of Example 1 are as follows: specific surface area is 17.35 m 2 / g, tap density is 1.68g / cm 3 , particle size distribution diameter distance is 0.76, sodium content is 60ppm, sulfur content is 633ppm, and D50 is 3.98μm.

[0053] Example 2

[0054] A method for preparing a high specific surface area and low sodium sulfur ternary precursor, comprising:

[0055] A 2.1 mol / L nickel-cobalt mixed salt solution was prepared according to the molar ratio of NiSO4, CoSO4, and MnSO4 of 60:10:30, and a 10 mol / L NaOH solution was used as a precipitant and an 8 mol / L ammonia solution was used as a complexing agent. The first reactor and the second reactor were respectively filled with water to the sampling port, and then stirred and the jacket water of the reactor was heated to 65°C. Ammonia solution was injected into the first reactor and the second reactor to prepare the bottom liquid before grooving, and the ammonia concentration in the first reactor and the second reactor was controlled at 4 g / L.

[0056] Coprecipitation reaction in the first reactor: nitrogen flow rate 1.5m 3 / h to ensure that the synthesis reactor is in a nitrogen atmosphere, adjust the homogenization speed to 800rpm, and start the nickel-cobalt-manganese salt solution pump, sodium hydroxide solution pump, and ammonia solution pump for coprecipitation reaction at the same time, control the salt liquid inflow to 5L / h, and after the liquid is inflow, stably control the temperature to 65°C, the ammonia concentration to 4g / L, the pH value to 11.8, and stably control the particle size D50 to 1.0μm-1.2μm, and the solid content to 120g / L-130g / L. At this time, the sample obtained is a primary particle with moderate thickness and a large flake shape, and a secondary particle with more porous nuclei;

[0057] Coprecipitation reaction in the second reactor: The material of the first reactor was pumped into the second reactor with a calculated pumping amount of 15L, the stirring speed was adjusted to 600rpm, and then the nickel-cobalt-manganese salt solution pump, the sodium hydroxide solution pump, and the ammonia solution pump were simultaneously used for coprecipitation reaction, and the salt inlet volume was controlled to be 3L / h. After the inlet, the temperature was stably controlled to be 65°C, the ammonia concentration was 4g / L, the initial pH value was 11.5, and the nitrogen flow rate was 1.5m 3 / h, after 4 hours of reaction, the nitrogen was replaced by air at a flow rate of 2m 3 / h, increase the salt flow rate by 0.5L / h every 4 hours, reduce the stirring speed by 3rpm, reduce the reaction pH by 0.03, and adjust the air flow rate to 2.5m / h when the particle size grows to 3μm. 3 / h, and stop the reaction when the particle size grows to 4μm. The output product is subjected to aging, clear liquid discharge, alkali washing, water washing and drying to obtain a high specific surface area and low sodium sulfur ternary precursor.

[0058] like Figure 2 As shown, the ternary precursor particles prepared in Example 2 have good sphericity, thick primary particles and small porosity.

[0059] The physical properties of the ternary precursor of Example 2 are as follows: specific surface area is 16.51 m 2 / g, tap density is 1.78g / cm 3 , particle size distribution diameter distance is 0.70, sodium content is 68ppm, sulfur content is 656ppm, and D50 is 4.02μm.

[0060] Example 3

[0061] A method for preparing a high specific surface area and low sodium sulfur ternary precursor, comprising:

[0062] A 2.1 mol / L nickel-cobalt mixed salt solution was prepared according to the molar ratio of NiSO4, CoSO4, and MnSO4 of 60:10:30, and a 10 mol / L NaOH solution was used as a precipitant and an 8 mol / L ammonia solution was used as a complexing agent. The first reactor and the second reactor were respectively filled with water to the sampling port, and then stirred and the jacket water of the reactor was heated to 65°C. Ammonia solution was injected into the first reactor and the second reactor to prepare the bottom liquid before grooving, and the ammonia concentration in the first reactor and the second reactor was controlled at 4 g / L.

[0063] Coprecipitation reaction in the first reactor: nitrogen flow rate 1.5m 3 / h to ensure that the synthesis reactor is in a nitrogen atmosphere, adjust the homogenization speed to 800rpm, and at the same time start the nickel-cobalt-manganese salt solution pump, the sodium hydroxide solution pump, and the ammonia solution pump for coprecipitation reaction, control the salt liquid inflow to 5L / h, and after the liquid is inflow, stably control the temperature to 65°C, the ammonia concentration to 4g / L, the pH value to 11.7, and stably control the particle size D50 to 1.2μm-1.4μm, the solid content to 120g / L-130g / L, and the sample obtained at this time is a primary particle with moderate thickness and a large flake shape, and a secondary particle with more porous nuclei;

[0064] Coprecipitation reaction in the second reactor: The material of the first reactor was pumped into the second reactor with a calculated pumping amount of 15L. The stirring speed was adjusted to 600rpm. Then, the nickel-cobalt-manganese salt solution pump, the sodium hydroxide solution pump, and the ammonia solution pump were simultaneously used for coprecipitation reaction. The salt inlet was controlled to be 3L / h. After the inlet, the temperature was stabilized at 65°C, the ammonia concentration was 4g / L, the initial pH value was 11.1, and the nitrogen flow rate was 1.5m 3 / h, after 4 hours of reaction, the nitrogen was replaced by air at a flow rate of 2.5m 3 / h, increase the salt flow rate by 1L / h every 4 hours, reduce the stirring speed by 10rpm, reduce the reaction pH by 0.02, and adjust the air flow rate to 3m when the particle size grows to 3μm 3 / h, and stop the reaction when the particle size grows to 4μm. The output product is subjected to aging, clear liquid discharge, alkali washing, water washing and drying to obtain a high specific surface area and low sodium sulfur ternary precursor.

[0065] like Figure 3 As shown, the ternary precursor particles prepared in Example 3 have good sphericity, thin primary particles and large porosity.

[0066] The physical properties of the ternary precursor of Example 3 are as follows: specific surface area is 18.76 m 2 / g, tap density is 1.54g / cm 3 , particle size distribution diameter distance is 0.78, sodium content is 62ppm, sulfur content is 667ppm, and D50 is 4.05μm.

[0067] Comparative Example 1

[0068] The difference between Comparative Example 1 and Example 1 is that the reaction temperature is different, and the reaction temperature is adjusted from 65° C. to 75° C. The coprecipitation reaction temperature in the first reactor of Comparative Example 1 is 75° C., and the coprecipitation reaction temperature in the second reactor of Comparative Example 1 is 75° C.

[0069] The physical properties of the ternary precursor of Comparative Example 1 are as follows: specific surface area is 20.35 m 2 / g, tap density is 1.68g / cm 3 , particle size distribution diameter distance is 0.76, sodium content is 80ppm, sulfur content is 983ppm, and D50 is 3.98μm.

[0070] Comparative Example 2

[0071] The difference between Comparative Example 2 and Example 1 is that the initial pH value of the coprecipitation reaction in the second reactor is different, and the initial pH value of Comparative Example 2 is 11.

[0072] The physical properties of the ternary precursor of Comparative Example 2 are as follows: the specific surface area is 23.56 m 2 / g, tap density is 1.42g / cm 3 , particle size distribution diameter distance is 0.81, sodium content is 75ppm, sulfur content is 865ppm, and D50 is 4.03μm.

[0073] Comparative Example 3

[0074] The difference between Comparative Example 3 and Example 1 is that the pH of the coprecipitation reaction in the first reactor is 11.9, and crystal nuclei with a particle size D50 of 0.8 μm to 1.0 μm are obtained.

[0075] The physical properties of the ternary precursor of Comparative Example 3 are as follows: the specific surface area is 14.22 m 2 / g, tap density is 1.82g / cm 3 , particle size distribution diameter distance is 0.78, sodium content is 78ppm, sulfur content is 832ppm, and D50 is 3.99μm.

[0076] The ternary precursors prepared in Examples 1-3 and Comparative Examples 1-3 were mixed with lithium hydroxide, ball milled for 4 hours to make them uniformly mixed, and heat treated in a tube furnace at a heating rate of 1°C / min, first heated to 600°C for 6 hours, then heated to 1000°C for 8 hours, and then naturally cooled, crushed, screened, and surface treated to obtain a ternary positive electrode material; the positive electrode material was then assembled with raw materials such as the treated metal lithium sheet negative electrode and lithium hexafluorophosphate electrolyte into a lithium ion battery. The performance of the lithium ion battery was measured and shown in Table 1 below.

[0077] Table 1

[0078] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Capacity / mAh / g 188 187 189 173 181 183 magnification 1C 1C 1C 1C 1C 1C First effect 89% 87% 88% 82% 85% 84% Voltage / V 2.8-4.25 2.8-4.25 2.8-4.25 2.8-4.25 2.8-4.25 2.8-4.25 Cycle performance / times 3200 3300 3100 2700 2900 2800

[0079] It can be seen from Table 1 that the electrical performance indicators of the ternary precursor materials of Examples 1-3 are better than those of Comparative Examples 1-3. Under the conditions of 2.8-4.25V and 1C / 1C charge and discharge regime, the first coulombic efficiency of Examples 1-3 is above 85%, and has higher capacity and rate performance.

[0080] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. A method for preparing a high specific surface area low sodium sulfur ternary precursor, characterized in that: include: Adding a nickel-cobalt-manganese salt solution, a precipitant and a complexing agent into a first reaction kettle, and performing a coprecipitation reaction under an inert atmosphere to obtain a crystal nucleus with a particle size D50 of 1.0 μm to 1.6 μm; The crystal nuclei, nickel-cobalt-manganese salt solution, precipitant and complexing agent are added to a second reaction kettle, and a coprecipitation reaction is first carried out under an inert atmosphere and then under an oxidizing atmosphere. The reaction is stopped when the product particle size D50 is 3.8 μm to 4.2 μm to obtain the high specific surface area low sodium sulfur ternary precursor.

2. The method for preparing a high specific surface area low sodium sulfur ternary precursor according to claim 1, characterized in that: The coprecipitation reaction in the first reactor includes: The inlet flow rate of nickel-cobalt-manganese salt solution is 4L / h~6L / h, and the inlet concentration is 1.8mol / L~2.4mol / L; The reaction temperature is 60°C to 70°C, the pH value is 11.6 to 11.8, and the homogenization speed is 700rpm to 800rpm.

3. The method for preparing a high specific surface area low sodium sulfur ternary precursor according to claim 1, characterized in that: The coprecipitation reaction is first carried out under an inert atmosphere, comprising: The initial crystal nucleus content of the reaction is 120g / L to 130g / L; The inlet flow rate of nickel-cobalt-manganese salt solution is 2L / h~4L / h, and the inlet concentration is 1.8mol / L~2.4mol / L; The reaction temperature is 60°C to 70°C, the reaction time is 4h to 5h, the pH value is 11.1 to 11.5, and the homogenization speed is 600rpm to 700rpm.

4. The method for preparing a high specific surface area low sodium sulfur ternary precursor according to claim 3, characterized in that: The coprecipitation reaction is carried out under an oxidizing atmosphere, comprising: Increase the flow rate of nickel-cobalt-manganese salt solution by 0.5L / h to 1L / h every 4 to 12 hours; Reduce the homogenization speed by 2rpm to 10rpm every 4 to 12 hours; Lower the reaction pH by 0.02 to 0.04 every 4 to 12 hours; Initial air flow rate is 1m 3 / h~3m 3 / h, when the particle size D50 of the product is 2.8μm~3.2μm, increase the air flow rate by 0.4m 3 / h~0.6m 3 / h.

5. The method for preparing a high specific surface area low sodium sulfur ternary precursor according to claim 1, characterized in that: The precipitant is sodium hydroxide solution, and the inlet concentration is 6 mol / L to 12 mol / L; The complexing agent ammonia solution has an inlet concentration of 4 mol / L to 10 mol / L; Controlling the ammonia concentration in the first reaction kettle to be 1 g / L to 5 g / L; The ammonia concentration in the second reaction kettle is controlled to be 1 g / L to 5 g / L.

6. The method for preparing a high specific surface area low sodium sulfur ternary precursor according to claim 1, characterized in that: In the nickel-cobalt-manganese salt solution, the molar ratio of nickel, cobalt and manganese is X:Y:Z, satisfying X+Y+Z=1, and 0.6≤X<1, 0<Y<0.4 and 0<Z<0.

4.

7. The method for preparing a high specific surface area low sodium sulfur ternary precursor according to any one of claims 1 to 6, characterized in that: The high specific surface area and low sodium sulfur ternary precursor has a specific surface area of ​​18±2m 2 / g, tap density is 1.70±0.2g / cm 3 , particle size distribution diameter is 0.75±0.1, sodium content is <70ppm, sulfur content is <800ppm, and D50 is 4±0.2μm.

8. A high specific surface area low sodium sulfur ternary precursor, characterized in that: The preparation method is adopted according to any one of claims 1 to 7.

9. A positive electrode material, characterized in that: The positive electrode material is prepared by mixing the high specific surface area, low sodium and sulfur ternary precursor described in claim 8 with a lithium source.

10. A lithium ion battery, characterized in that: The positive electrode material of the lithium ion battery is the positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Novel small-particle ternary precursor and preparation method thereof

    CN113683129A

  • Preparation method of doped ternary precursor for improving sphericity degree of large particles

    CN116354412A

  • Preparation method and preparation device for ternary precursor material of sodium-ion battery

    CN117800404A

  • Nickel-cobalt-manganese ternary precursor with high specific surface area as well as preparation and application of nickel-cobalt-manganese ternary precursor

    CN117980271A

  • Nickel-based active material precursor for lithium secondary battery, preparation method thereof, nickel-based active material for lithium secondary battery formed therefrom, and lithium secondary battery including cathode including the nickel-based active material

    US20200058937A1

Cited By

  • Ultrahigh-nickel ternary precursor and preparation method thereof, positive electrode material, lithium ion battery and electric equipment

    CN120483291A

  • Manganese-rich precursor, preparation method thereof and positive electrode material

    CN121735324A

  • Manganese-rich precursor, preparation method thereof and cathode material

    CN121735324B